Software development of assembly sequence appraoch for table fan by using intergrated TRIZ, axiomatic design and Boothroyd-Dewhurst DFA - Tajul Arif, Zakaria (2008)
Price is one of the important packages that must have in a product so it can be more competent in market. Assembly cost is one of the major operations in manufacturing but always ignored during designing stage. Design is a process that needs creativity of an engineer. Theory Inventive Problem Solving (TRIZ) and Axiomatic Design (AD) is a method which provides guidelines for the designer to design a product. This project is aim to use develop a software by using the integrate approach of AD, TRIZ and DFMA to improve product design process. The software was developed by using Microsoft Visual Basic 6. The result of this research is software named Axiomatic-DFA. Comparative analysis will be done between current and proposed design. Using integration of AD and TRIZ, current design is improved in terms of Design for Assembly (DFA). Current parts will be analyzed using DFA method to know the level of assembly effectiveness. . The assembly effectiveness of current design will obtain, and will be set a datum. Then, integration of AD and TRIZ are used to generate the proposed design. A survey among possible customer is done and translates to the customer domain. Functional requirements are determined to satisfy customer requirement. If FR identified doesn’t meet the constrained or coupled, the process will continued with TRIZ method .Using 3 TRIZ tools, the proposed design should be obtained in the end of the analysis. Proposed design is evaluated and selected based on Pugh method. DFA analysis of optimized design is done and comparative analysis is made between the current and proposed design. The final result of the project shows that design efficiency is increased by 108.2 %.The develop software then checked for its validity in terms of its result by comparing to the actual software that is in the market already the Boothroyd-Dewhurst DFA. The comparison shows that the newly-develop Axiomatic-DFA got an accuracy in the range of 94.6-99.4 % in terms of design efficiency.